2022
DOI: 10.1038/s41586-022-04822-x
|View full text |Cite|
|
Sign up to set email alerts
|

Genome evolution and diversity of wild and cultivated potatoes

Abstract: Potato (Solanum tuberosum L.) is the world’s most important non-cereal food crop, and the vast majority of commercially grown cultivars are highly heterozygous tetraploids. Advances in diploid hybrid breeding based on true seeds have the potential to revolutionize future potato breeding and production1–4. So far, relatively few studies have examined the genome evolution and diversity of wild and cultivated landrace potatoes, which limits the application of their diversity in potato breeding. Here we assemble 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 106 publications
13
140
0
Order By: Relevance
“…However, the molecular mechanism of flowering and branching remains elusive. Some proteins interacting with StSP6A have been reported, including StFDL1, StABL1, StSWEET11, and BRC1b [ 6 , 7 , 8 , 9 , 11 ]. It is important to explore whether there are some other unknown StSP6A interactors involved in other functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanism of flowering and branching remains elusive. Some proteins interacting with StSP6A have been reported, including StFDL1, StABL1, StSWEET11, and BRC1b [ 6 , 7 , 8 , 9 , 11 ]. It is important to explore whether there are some other unknown StSP6A interactors involved in other functions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that StSP6A is involved in branching and flowering [ 9 , 10 ]. A TCP transcription factor, BRANCHED1b (BRC1b), interacts with StSP6A to promote dormancy and repress tuberization [ 9 , 11 ]. Under SD conditions, the development of flower buds is repressed by the tuberization signal StSP6A [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 c ; Hardigan et al 2017 ). A recent study on the potato pan-genome shows that both ILS and hybridization/introgression have contributed to blurring evolutionary relationships between wild potato species and landraces ( Tang et al 2022 ).…”
Section: Potatomentioning
confidence: 99%
“…Confounding signals: The adaptive hybridization/introgression signal can be easily confounded with incomplete lineage sorting (ILS; Pamilo and Nei 1988 ; Doyle 1992 ; Maddison 1997 ; Rosenberg and Nordborg 2002 ; Blanco-Pastor et al 2011 ; Tang et al 2022 ). Analyses that distinguish both patterns (such as the four taxon f 4 [ Patterson et al 2012 ] or f d [ Martin et al 2015 ] statistics or the five-taxon D FOIL [ Pease and Hahn 2015 ] statistic, which are all related to the genome-wide summary ABBA-BABA test [ Green et al 2010 ]) are essential tools for detecting introgression.…”
Section: The Adaptive Significance Of Introgressionmentioning
confidence: 99%
“…Phased, chromosome-level genome assemblies of heterozygous diploid and tetraploid potatoes are also available [17][18][19] . Pan-genome studies of crop plants including potato have also emerged, that shed light on the extensive genetic variation in these species [20][21][22][23] . To reduce the genomic complexity and sequencing costs, resistance gene enrichment sequencing (RenSeq) and RLP/K enrichment sequencing (RLP/KSeq) technologies were developed to sequence plant NLR and PRR gene repertoires [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%